2017
DOI: 10.3390/s17040672
|View full text |Cite
|
Sign up to set email alerts
|

Using an Active-Optical Sensor to Develop an Optimal NDVI Dynamic Model for High-Yield Rice Production (Yangtze, China)

Abstract: The successful development of an optimal canopy vegetation index dynamic model for obtaining higher yield can offer a technical approach for real-time and nondestructive diagnosis of rice (Oryza sativa L) growth and nitrogen (N) nutrition status. In this study, multiple rice cultivars and N treatments of experimental plots were carried out to obtain: normalized difference vegetation index (NDVI), leaf area index (LAI), above-ground dry matter (DM), and grain yield (GY) data. The quantitative relationships betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Monostori et al [30] reported for wheat that SPAD values should be calibrated for each cultivar to obtain more accurate N diagnosis and yield prediction. The present work and previous research [46,47] suggest that in order to use absolute sufficiency values, regardless of the cultivar, that procedures to normalize absolute chlorophyll meter measurements should be developed.…”
Section: Assessment Of Cultivar Effects On Optical Sensor Measurementsmentioning
confidence: 80%
“…Monostori et al [30] reported for wheat that SPAD values should be calibrated for each cultivar to obtain more accurate N diagnosis and yield prediction. The present work and previous research [46,47] suggest that in order to use absolute sufficiency values, regardless of the cultivar, that procedures to normalize absolute chlorophyll meter measurements should be developed.…”
Section: Assessment Of Cultivar Effects On Optical Sensor Measurementsmentioning
confidence: 80%
“…We examined N distribution by evaluating color differences between upper and lower leaves, and via differential diagnosis of rice N status. A previous study found that chlorophyll content reflected N nutritional status, but was significantly influenced by variety, site, and year of experimentation [31]. A previous study indicated that data normalization prior to modeling eliminated differences caused by variety, soil types, and management strategies, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Calculating relative SPAD values requires the use of a non-N-limiting treatment as a control, reducing the utility of the method regarding on-farm N diagnosis [30]. SPAD value differences among varieties, and variations in production levels, can be eliminated by normalizing experimental data before modeling [31]. Therefore, some studies have used different normalized SPAD index (NDSI) values to reduce the effects of variation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several attempts have been made to eliminate the influence of factors that affect SPAD readings by normalizing the SPAD reading (Liu et al., ), which can overcome the negative influences of cultivars, locations, years, and growing stages (Wang, Zhu, Jiang, & Cao, ). However, N regulation strategies based on normalized SPAD values have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%